The Impact of Corporate Image of PT XYZ towards Job Applicant Attraction in Surabaya - Janice, Janice; Leosaputro, Jessica Inez (iBuss Management, 2014)
Human capital is considered as a crucial factor that can impact company performance. It is expected that Indonesia will face talent scarcity (BCG, 2013). In Surabaya, PT XYZ also competes with other companies to attract the best talents to join the company. This research is conducted with the aim to find out the effect of corporate image in attracting job applicants. The data was gathered using simple random sampling by distributing questionnaires to 109 respondents in Surabaya. The data was analyzed by using Multiple Linear Regression Analysis. The result shows that the corporate image simultaneously has significant impact on job applicant attraction. Meanwhile, as individual dimension, employer image and CSR image has significant impact toward job applicant attraction. Â Keywords: Human capital, corporate image, job applicant attraction, regression.